Microstructure and Stability of Non-Protein Stabilized Oil-in-Water Food Emulsions Measured by Optical Methods - Quintana, Juan Manuel (2002)
The microstructure and stability of oil-in-water emulsions, stabilized with non-protein emulsifiers (sorbitan esters), were analyzed as a function of emulsification time, rotor speed, hydrophilic-lipophilic balance (HLB), and ionic strength. Sauter average dia (D[3,2]) were determined from micrographs. Back-scattered light data were analyzed and a method to determine creaming rates of the systems was proposed. Creaming rates showed that the relationship between emulsion stability and HLB was non-linear. Addition of NaCl raised creaming rates, resulting in decreased stability, while micrographs showed the presence of flocs. Results were discussed taking account of interactions present in the system.